8-Hydroxyeicosapentaenoic Acid Reduces Adipogenesis and Inflammation in 3T3-L1 Adipocytes. (14th June 2022) - Zu, Yujiao; Moustaid-Moussa, Naima; Mikhael, Mark; Scoggin, Shane; Pal, Anandita; Shaikh, Saame Raza
Abstract: Objectives: Obesity is a complex disease and a chronic low-grade inflammatory state, which contributes to metabolic dysfunctions. Eicosapentaenoic acid (EPA), an n-3 fatty acid in fish oil, exerts anti-obesity and anti-inflammatory effects. Our previous study indicated that EPA lowered fat mass in obese female mice, potentially through increased biosynthesis of 8-hydroxyeicosapentaenoic acid (HEPE), an EPA-derived metabolite. Therefore, the objective of this study was to elucidate mechanisms underlying 8-HEPE effects on adipogenesis and inflammation using cultured 3T3-L1 cells. We hypothesized that 8-HEPE is more effective than EPA in reducing lipid accumulation and inflammatory genes in vitro. Methods: Murine 3T3-L1 adipocytes were cultured and differentiated with 5μM EPA, 18-HEPE, 8-HEPE, or control. Differentiated adipocytes were fixed and stained with Oil-Red-O solution and lipid content measured spectrophotometrically. To determine anti-inflammatory effects, 3T3-L1 pre- and differentiated cells were treated as above with or without lipopolysaccharide (LPS). Medium and cells were collected to measure interleukin-6 (IL-6) levels and genes involved in adipogenesis and inflammation. Results were analyzed by one-way ANOVA followed by a Tukey post-hoc test (GraphPad Prism). Results: 3T3-L1 cells differentiated with 8-HEPE had lower lipid content than control (p < 0.01). Consistently, 8-HEPE treated cells expressed a lower level of fatty acid synthesis gene, like acetyl-CoA carboxylase and fatty acid synthase than control (p = 0.059 and p = 0.042). And 8-HEPE exhibited promising anti-inflammatory effects by downregulating the IL-6 cytokine level in both LPS stimulated pre- and differentiated 3T3-L1 cells (p < 0.05). LPS-stimulated differentiated cells treated with 8-HEPE expressed a lower level of the inflammatory gene, IL-6 (p = 0.017), and a trend toward a higher level of the anti-inflammatory gene, arginase 1 (p = 0.067), than LPS control. Conclusions: Our findings indicate that the 8-HEPE has potent antiadipogenic and anti-inflammatory effects in vitro, and merit further investigations in vivo to determine whether EPA's effects are mediated by its downstream metabolite 8-HEPE. Our findings further demonstrate the importance of studying the role of EPA-derived metabolites in obesity and inflammation. Funding Sources: None.